Assessing the eco-efficiency of industrial parks recycling transformation: Evidence from data envelopment analysis (DEA) and fuzzy set qualitative comparative analysis (fsQCA) - Lei, Zhen; Wei, Junrong (Frontiers in Environmental Science, 2023)
Industrial parks are essential for promoting regional economic development, yet their linear growth model has become unsustainable. Hence, implementing the industrial park recycling transformation (IPRT) is necessary and urgent. However, the current literature on IPRT performance evaluation and improvement has not kept up with practical developments. This study aims to evaluate the eco-efficiency of IPRT and identify the variables and configurations that affect its enhancement. To achieve this, the authors employed super-efficiency data envelopment analysis and fuzzy set qualitative comparative analysis to analyze data collected from 21 IPRT demonstration pilot parks. Drawing on the Technology-Organization-Environment framework, this study identified three configurations with high eco-efficiency and two configurations with non-high eco-efficiency for IPRT. The findings indicate that eco-efficiency varies significantly among different parks and is the result of multiple factors and interactions, with environmental supervision playing a pivotal role. Additionally, the results suggest that the local economic development level and the technological capacity of parks are substitutable. Parks in regions with modest economies tend to focus on environment-technology-oriented transformations, while external factors drive IPRT of parks in areas with developed economies. These findings offer guidance for parks to adopt appropriate strategy profiles and provide policy options for governments.